2008
DOI: 10.1073/pnas.0710650105
|View full text |Cite
|
Sign up to set email alerts
|

Splicing mediates the activity of four putative cellular internal ribosome entry sites

Abstract: A growing number of cellular mRNAs are thought to possess internal ribosome entry sites (IRESs), sequences that permit translation of a transcript independent of its 5 end and cap structure. Although dicistronic assays are the canonical method of testing sequences for IRES activity, they may produce false-positive results if unanticipated monocistronic RNAs arise from the dicistronic construct used. Using a dicistronic reporter system and a green fluorescent protein-tagged retrovirus to evaluate six previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 45 publications
2
75
2
Order By: Relevance
“…The anti-apoptotic protein XIAP, an important factor for tumor cell survival and resistance to apoptosis after treatment with anti-cancer agents (46 -48), is regulated by a translational mechanism (36). Initially it was thought that this mRNA contained an IRES (36), but a subsequent study showed that a 3Ј splice site was necessary for apparent IRES function (49). The mRNA encoding c-Myc shifts to heavier polysomes under conditions of reduced cap-dependent translation (45), and evidence has been presented that it contains an IRES (37).…”
Section: Discussionmentioning
confidence: 99%
“…The anti-apoptotic protein XIAP, an important factor for tumor cell survival and resistance to apoptosis after treatment with anti-cancer agents (46 -48), is regulated by a translational mechanism (36). Initially it was thought that this mRNA contained an IRES (36), but a subsequent study showed that a 3Ј splice site was necessary for apparent IRES function (49). The mRNA encoding c-Myc shifts to heavier polysomes under conditions of reduced cap-dependent translation (45), and evidence has been presented that it contains an IRES (37).…”
Section: Discussionmentioning
confidence: 99%
“…So this ubiquitous presence of a 5 0 -proximal splice donor site poses a strong risk of mis-splicing to any cryptic 3 0 -splice site present in the putative IRES under test (Fig. 3C), as shown by the finding that when all potential 5 0 -splice sites in the 5 0 -UTR and the upstream cistron (in this case coding for Gaussia luciferase) were inactivated by mutations, the BiP, NRF, VEGF, and XIAP 5 0 -UTRs, as well as the eIF4GI 5 0 -UTR reported by Gan and Rhoads (1996), failed to show significant IRES activity above the "no IRES" control, or the b-globin 5 0 -UTR, although the EMCV IRES positive control yielded high activity (Baranick et al 2008). In the same publication a sensitive assay involving incorporating the IRES and a GFP reporter into a murine leukaemia virus proviral DNA (Fig.…”
Section: Kip2mentioning
confidence: 99%
“…Indeed it has been shown that in a Krebs-2 in vitro system, or in an RNA transfection assay, an mRNA with the 900 nt (60% GC) LINE-1 5 0 -UTR, is translated by the cap-dependent scanning mechanism at 50% relative efficiency compared to the b-globin 5 0 -UTR (Dmitriev et al 2007). It should also be noted that some long 5 0 -UTRs with apparent IRES activity have subsequently been shown to be incompletely spliced variants with retained introns (Baranick et al 2008), for example the original eIF4GI 5 0 -UTR studied by Gan and Rhoads (1996), in contrast to the eIF4GI 5 0 -UTRs described by Johannes and Sarnow (1998) and Byrd et al (2005).…”
Section: Cellular Mrna Iressmentioning
confidence: 99%
See 1 more Smart Citation
“…3D), suggesting a potential IRES created by Alu exon inclusion. However, to confirm the identity of the IRES element definitively and to define its exact location in the Alu exon inclusion 5′-UTR requires substantial additional experimental efforts (39,40).…”
Section: Molecular Mechanisms Of Translational Regulation By Alu Exonsmentioning
confidence: 99%